Study on the interface of high specific energy High stability - Yin, Shuhan (Transactions on Engineering and Technology Research, 2024)
High nickel terterial oxide, with high specific capacity and low cost advantages, is the preferred positive electrode for high specific energy lithium-ion power batteries at present. However, the high nickel ternary cathode material is easy to have side reactions with the electrolyte in the high delithium state, which can not only lead to the dissolution of transition metal ions and the formation of the surface salt phase, but also cause the lattice oxygen loss and surface interface side reactions, resulting in rapid attenuation of electrode capacity. In this paper, the development history and structural characteristics of high nickel ternary cathode materials are introduced, and the surface interface problems leading to capacity attenuation and structural degradation are comprehensively analyzed. From this perspective, three effective strategies for improving electrochemical performance of high nickel ternary cathode materials are summarized. Finally, by describing the advantages and disadvantages of these layered cathode materials, the challenges faced by these layered cathode materials are discussed, and it is pointed out that in the future, composite modification strategies should be adopted to optimize their structures and improve their properties.